Mental health and the COVID-19 pandemic - Zalewska, Anna; Marta (Kwartalnik Naukowy Fides et Ratio, 2022)
Introduction: The disease caused by the SARS-CoV-2 virus is a significant threat to human life and health. It is highly contagious and therefore spreads rapidly and is fatal in severe cases. The main purpose of this article is to present the mental health impact of the COVID-19 pandemic.Method: Based on the review of the current literature based on the EBM (Evidence-Based Medicine) paradigm, the main mental health problems resulting from the pandemic are presented. During data collection, the PubMed search engine servicing the MEDLINE database and Google Scholar were used. The criterion that was used when searching for articles were papers published from 2020 available in Polish or English.Results: The SARS-CoV-2 virus infection itself, as well as the restrictions related to the pandemic, cause a number of negative consequences for mental health. They can manifest themselves as single symptoms or complexes of symptoms, as well as disorders or groups of disorders and complex problems of a psychopathological nature. All these phenomena can overlap and appear in the course of COVID-19, as well as its complications. The data available from the literature review show that during a pandemic, about 30% of people suffer from mental disorders, and over 50% of respondents report psychological distress. Mental health neglect during a pandemic may cause worsening disorders that may reveal themselves over the years.Conclusions: There are many options for combating the negative effects of a pandemic, which can be introduced at different levels. The impact of COVID-19 on the mental state of individual populations should be investigated and precisely defined, as it is necessary for planning short-term and long-term interventions in the areas of: medical, information and organizational. The full potential of many scientific disciplines should be used to contain the spread of the negative effects of a pandemic.